Sertifikasi Halal Produk Makanan Sebagai Perlindungan Konsumen Muslim; Studi di Lembaga Pengkajian Pangan Obat-Obatan dan Kosmetika-Majelis Ulama Indonesia Sulawesi Tenggara - Sodiman, Sodiman (Li Falah: Journal of Islamic Economics and Business, 2018)
The study of halal food has grown rapidly, not only in countries that are predominantly Muslim, but also in Muslim minority countries. The purpose of this article is to reveal how religious norms regarding halal and thoyy food have proceeded into the technoscientific certification of halal certification in Indonesia which is predominantly Muslim through microscopic studies at the Institute for the Study of Food Medicine and Cosmetics-Indonesian Ulama Council (LPPOM-MUI) Southeast Sulawesi. The study used a qualitative approach with primary data sourced from the institutions and actors involved in the certification process at LPPOM-MUI Southeast Sulawesi, namely directors, employees, auditors and the Southeast Sulawesi MUI Fatwa Council, business actors and consumers of certified food products. Data collection through in-depth interviews, observation, and document studies. Data processing used data reduction techniques, data  classification, data display, data interpretation and conclusions. This study found, first, halal techno-scientifications were run by LPPOM-MUI through standardization (1) of materials, (2) products, (3) production facilities, (4) written procedures for critical activities, and (5) search capabilities. Second, the role of LPPOM-MUI in protecting Muslim consumers as institutions and actors guarding halal standards for products that will circulate to the public. The researcher argues that the impact of halal certification is the protection of consumers (Muslims). However, no illicit (haram) certification is applied to products that are not halal certified to be a gapand space for the circulation of food products, medicines and cosmetics that are not halal to the market (society).